Pengaruh Kualitas Sistem, Kualitas Informasi, Dan Kualitas Layanan Terhadap Kepuasan Pengguna Aplikasi Flip (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Jenderal Achmad Yani) - Fitri Adelfi; Nunung Aini Rahmah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the influence of System Quality, Information Quality, and Service Quality on User Satisfaction in Flip Applications (Case Study on Students of the Faculty of Economics and Business, Jenderal Achmad Yani University). The analysis technique used in this study was the accidental sampling technique, with 335 samples from 2072 populations directly related to user satisfaction. All respondents filled out the research questionnaire via Google Forms. The results of the study show System Quality significantly negatively affects User Satisfaction with the Flip Application, Information Quality does not affect User Satisfaction in the Flip Applicatio,. Quality of Service has a positive significant influence on User Satisfaction in the Flip Application. Keywords: System Quality, Information Quality, Service Quality, User Satisfaction